Emotion in the Area of Entrepreneurship: An Analysis of Research Hotspots - Lu, Xifeng; Xiong, Yiyu; Lv, Xingqun; Shan, Biaoan (Frontiers in Psychology, 2022)
The application of emotion in economic management is gaining attention. As an important irrational factor, personal emotion often plays a significant role in business decision-making activities. In the field of entrepreneurship, emotion also plays a crucial role, and more and more scholars are focusing on this interdisciplinary issue. However, the current research on emotion in entrepreneurship is still fragmented, and there is an urgent need for a more scientific and systematic approach to comprehensively organize the literature in this field, so as to lay the foundation for researchers to further research on emotion in entrepreneurship. In this study, VOSviewer was used to analyze the existing literature, and the results showed that the current research on emotion in the field of entrepreneurship mainly focuses on five research themes, namely, emotion and college students' entrepreneurship, family emotion and entrepreneurship, the role of emotion in successful entrepreneurship, emotional problems under the influence of entrepreneurial failure, and entrepreneurial passion.